A new amino alcohol NpyNimineNamineOalcohol-donor ligand: coordination toward zinc(II) and cadmium(II) halides and enantioselective products. Issue 20 (18th October 2017) - Hakimi, Mohammad; Ahmadi, Sheida; Mardani, Zahra; Mohr, Fabian
Abstract: In the present work a new ligand, 2-(2-(phenyl(pyridin-2-yl)methyleneamino)ethylamino)ethanol (L), and its Zn(II) and Cd(II) complexes, [Zn(L)Br2 ] (1 ), [Cd(L)Br2 ] (2 ) and [Cd(L)I2 ] (3 ), have been synthesized and characterized by elemental analysis, FT-IR, Raman and 1 H NMR spectroscopies as well as X-ray crystallography. All complexes are isostructural and their metal ions have distorted square pyramidal geometry with an MN3 X2 (X: Br, I) environment. During the complexation process, the amine group of the ligand becomes a chiral center. In the solid-state, an R -configuration was observed in all three complexes. Furthermore, the molecules form intermolecular C–H⋯O, C–H⋯X and O–H⋯X (X: Br, I) hydrogen bonds in the solid-state. Abstract :